The Age Of The Unthinkable - "Ramo, Joshua Cooper." (New York)
Includes bibliographical references and index.
Keywords: UNITED STATES -- FOREIGN RELATIONS -- 2001-2009.;UNITED STATES -- MILITARY POLICY.;WORLD POLITICS -- 21ST CENTURY